Analysis of the Vibration Characteristic of Rolling Bearing-Rotor System of Machine Tool Spindle - Si Zhanfeng; Ma Wei; Li Jishun; Xue Yujun; Yang Fang (Jixie chuandong)
The non- linear bearing force in the working state of the rolling bearing is deduced and non-linear dynamics equations of a system are established. The system axis path chart,the bifurcation diagram and the Poincare figure are drawn in Matlab and used to analyze the characteristics of the system vibration with the different parameters. The numerical method is used to solve the equations and the displacement values of system vibration are obtained. The results show that the change of the non- linear bearing force will cause the vibration of the system and bifurcation phenomena will appear in the system. The speed,damping and radial force are important parameters that influence the vibration. By choosing reasonable working parameters,the vibration of system can be reduced and the stability of the system can be improved.